Risk Analysis of Pesticide Poisoning to Farmers in Kenagarian Simpang Tanjung Nan IV, Solok Regency - Arlinda, Sari; Mukhlis, Mukhlis; Suksmerri, Suksmerri; Wijayantono, Wijayantono (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Introduction: Farmers use synthetic pesticides to enhance agricultural productivity, reduce or eliminate yield losses, and maintain high product quality. Although synthetic pesticides play a crucial role in increasing agricultural productivity, they also pose risks to the health of farmers. Long-term exposure to pesticides is a risk for farmers and can cause various types of cancer, such as digestive system cancer, stomach cancer, esophageal cancer, lung cancer, intestinal cancer, bladder cancer, and lymphoma. Pesticides also exhibit mutagenic and teratogenic properties. The aim of this study is to determine the risk analysis of pesticide poisoning to farmers in Kenagarian Simpang Tanjung Nan IV, Solok Regency. Method: This research is a descriptive observational study with a cross-sectional design and a field study method using Environmental Health Risk Analysis (EHRA) by measuring pesticide levels in each village and farmers residing in the area. The study was conducted from July to December 2023. Results: The study shows an average duration of exposure for farmers of 15.69 years with an average daily exposure of 7 hours. Pesticide concentrations in the air, soil, and water exceed the quality standard value of 0.1 mg/L. All real-time Risk Quotient (RQ) values indicate that farmers are at risk of pesticide poisoning.